PEMBERDAYAAN EKONOMI MASYARAKAT DESA CURUGBITUNG MELALUI PENGUATAN UMKM DAN LITERASI KEUANGAN SYARIAH - Awaludin, Muhamad Robie; Muslim, Fahmi; Alfiyah, Pipin; Mauladin, Zaenal; Amartabela, Yolanda; Azan, M.Ismul; Al Kautsar, Muhammad Hikmatul (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
The goal of this community service initiative is to strengthen micro, small, and medium enterprises (MSMEs) and improve Islamic financial literacy in Curugbitung Village, Nanggung District, Bogor Regency. Activities included observing MSME potential, providing guidance, training, business mentoring, and collaborative assessments. The results showed that 80% of participants understood Islamic financial concepts such as musyarakah, murabahah, and mudharabah. Furthermore, after receiving mentoring, many businesses experienced a 15-20% increase in turnover, and 70% of MSMEs were able to prepare basic financial reports. Furthermore, the program helped build the community's social capital, including digital marketing skills and self-confidence. Overall, this activity demonstrated that the implementation of Islamic financial literacy and MSME empowerment successfully promoted community economic independence based on Islamic principles.